Smart Solar Micro-exchangers for Sustainable Mobility of University Camps - Rosa-Jiménez, Carlos; De la Bandera Cascales, Isabel; Mora-López, Llanos; Sidrach-de-Cardona-Ortin, Mariano; Álvarez-Gil, Antonio; Camacho-Mérida, Lourdes; Casaucao-Tenllado, Inmaculada; Delgado-Fernández, Samuel; García-Moreno, Alberto Enrique; Márquez-Ballesteros, María José; Mendoza Ruiz, Jessica; Morales-Martín, Alejandro; et al. (IOP, 2020)
A significant number of universities have several campuses located in urban or rural settings, or with scattered university buildings that require the use of means of transportation. This implies the mobility and potential displacement of a large community of students, professors and researchers. The use of electric bicycles (e-bikes) is an intermediate alternative between the bicycle and electric cars. It can be an important stimulus for the promotion of the decarbonisation of the University Campus, avoiding the traffic congestion and reducing space requirements for parking. This paper presents the smart solar micro-exchanger model managed through a sustainable mobility web platform, applied to the case study of the University of Malaga (Spain). It is a solar charging station for e-bike, whose design is based on the principles of solar architecture (providing great security to e-bike). It managed by a web platform and app that allows the user to make reservations and learn about the savings in CO2 emissions. The system allows performing an aerobic sports activity without sweating problems when you reach the job. The platform also incorporates a database of quiet and safe routes for e-bike users.
Publicado el resumen en: https://www.wmcaus.org/files/WMCAUS2020_Book.pdf. Pendiente de publicación de las contribuciones en IOP Conference Series: Materials Science and Engineering.
Keywords: Universidad de Málaga - Aspectos ambientales; Bicicletas; Energía solar; Ebike; Sustainable mobility; Campus mobility; Solar e-charger; Bicicletas eléctricas; Movilidad sostenible